PENERAPAN METODE SDLC (SYSTEM DEVLOPMENT LIFE CYCLE) PADA WEBSITE PENJUALAN PRODUK VAPOR: APPLICATION OF SDLC (SYSTEM DEVLOPMENT LIFE CYCLE) METHOD ON VAPOR PRODUCT SALES WEBSITE - Ichsan Raksa Gumilang (JURAL RISET RUMPUN ILMU TEKNIK, 2022)
Vapors or e-cigarettes are cigarettes with an evaporation process. One shop selling vapor products called the Independent Store sells various kinds of vapor products as well as liquids and other vapor equipment. This Independent Store store has problems in selling because it has not used an online-based sales system. Therefore, it is the desire of the researchers to be able to assist in the process of selling vapor products at the Independent Store store by creating a website. In the process of creating a website for selling vapor products, method is used SDLC (System Development Life Cycle) the waterfall model . With the hope of helping shop owners and employees in the sales process.